Establishing a Reforestation Baseline in Community Forestry in Leyte - Herbohn, John (Annals of Tropical Research, 2003)
This paper discusses the collection of information to establish a reforestation baseline in community forestry in Leyte. Philippines. The paper outlines how baseline information about current nursery practices, including an assessment of seedling availability and quality and current levels of tree planting, will be used to assess the testing of intervention measures designed to overcome impediments identified as part of an ongoing research project.